Management of spontaneous intracerebral hemorrhage - Veltkamp, Roland; Purrucker, Jan (Current neurology and neuroscience reports, 2017)
Purpose of ReviewWe review the current evidence for medical and surgical treatments of spontaneous intracerebral hemorrhage (ICH).Recent FindingsTherapy with hemostatic agents (e.g. factor VIIa and tranexamic acid) if started early after bleeding onset may reduce hematoma expansion, but their clinical effectiveness has not been shown. Rapid anticoagulation reversal with prothrombin concentrates (PCC) plus vitamin K is the first choice in vitamin K antagonist-related ICH. In ICH related to dabigatran, anticoagulation can be rapidly reversed with idarucizumab. PCC are recommended for ICH related to FXa inhibitors, whereas specific reversal agents are not yet approved. While awaiting ongoing trials studying minimally invasive approaches or hemicraniectomy, the role of surgery in ICH remains to be defined. Therapies targeting downstream molecular cascades in order to prevent secondary neuronal damage are promising, but the complexity and multi-phased nature of ICH pathophysiology is challenging. Finally, in addition to blood pressure control, antithrombotic prevention after ICH has to consider the risk of recurrent bleeding as well as the risk of ischemic events.SummaryTreatment of acute ICH remains challenging, and many promising interventions for acute ICH await further evidence from trials.